2017
DOI: 10.3390/molecules22010074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Characterization, and Functional Analysis of Acetyl-CoA C-Acetyltransferase and Mevalonate Kinase Genes Involved in Terpene Trilactone Biosynthesis from Ginkgo biloba

Abstract: Ginkgolides and bilobalide, collectively termed terpene trilactones (TTLs), are terpenoids that form the main active substance of Ginkgo biloba. Terpenoids in the mevalonate (MVA) biosynthetic pathway include acetyl-CoA C-acetyltransferase (AACT) and mevalonate kinase (MVK) as core enzymes. In this study, two full-length (cDNAs) encoding AACT (GbAACT, GenBank Accession No. KX904942) and MVK (GbMVK, GenBank Accession No. KX904944) were cloned from G. biloba. The deduced GbAACT and GbMVK proteins contain 404 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
4
18
0
2
Order By: Relevance
“…In plants, information about the roles of MVK and MVD is quite limited compared to yeast [59]. However, the latest study of MVK in Gingko biloba discovered that overexpression of MVK led to the accumulation of the terpene trilactone [60]. In P. minor , the accumulation of MVK at 6 dpi may contribute to sesquiterpene biosynthesis, although the rate-limiting enzyme had its highest expression at 9 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, information about the roles of MVK and MVD is quite limited compared to yeast [59]. However, the latest study of MVK in Gingko biloba discovered that overexpression of MVK led to the accumulation of the terpene trilactone [60]. In P. minor , the accumulation of MVK at 6 dpi may contribute to sesquiterpene biosynthesis, although the rate-limiting enzyme had its highest expression at 9 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the MVA pathway may also have a minimal contribution to the biosynthesis of TTLs. Up to now, some of genes encoding enzymes involved in MVA pathway have been cloned and characterized from G. biloba , including HMGR [ 29 ], mevalonate diphosphate decarboxylase (MVD) [ 10 ], mevalonate kinase (MVK) and acetyl-CoA C -acetyltransferase (AACT) [ 30 ]. However, the HMGS genes in G. biloba are poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported that DXS plays a crucial role in the biosynthesis of the monoterpene precursor [30][31][32][33]. Additionally, GbMVK is highly expressed in the leaves, roots and stems of Ginkgo biloba, which is related to the production of the main active substance in terpene trilactone biosynthesis [34]. In the classical MVA pathway, PMVK can catalyse the transformation of mevalonate-5P into mevalonate-5PP, which is subsequently subjected to decarboxylation catalysed by mevalonate 5-diphosphate decarboxylase [14].…”
Section: Discussionmentioning
confidence: 99%